2013
DOI: 10.1155/2013/593181
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Red Ginseng in Type 1 and Type 2 Diabetes in Animals

Abstract: Diabetes mellitus (DM) is one of the most modern chronic metabolic diseases in the world. Moreover, DM is one of the major causes of modern neurological diseases. In the present study, the therapeutic actions of Korean red ginseng were evaluated in type 1 and type 2 diabetic mouse models using auditory electrophysiological measurement. The comprehensive results from auditory brainstem response (ABR), auditory middle latency response (AMLR), and transient evoked otoacoustic emission (TEOAE) demonstrate auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…The selected RGE dose in this study is in the range of effective dose without significant toxicity and showed similar plasma concentrations of Rb1, Rb2, and Rc (5.3-15.8 nM in rats and 6.2-12.7 nM in human subjects) [19,33]. In numerous animal studies, the RGE dose has ranged from 200 mg/kg to 2.0 g/kg (i.e., 3-15 mg/kg of total ginsenosides) [36,37]. In human studies, RGE was administered to diabetic patients for 4 to 24 weeks at doses of 2.7-6.0g/day, which usually contained 50-100 mg ginsenosides/day [20,38].…”
Section: Discussionsupporting
confidence: 51%
“…The selected RGE dose in this study is in the range of effective dose without significant toxicity and showed similar plasma concentrations of Rb1, Rb2, and Rc (5.3-15.8 nM in rats and 6.2-12.7 nM in human subjects) [19,33]. In numerous animal studies, the RGE dose has ranged from 200 mg/kg to 2.0 g/kg (i.e., 3-15 mg/kg of total ginsenosides) [36,37]. In human studies, RGE was administered to diabetic patients for 4 to 24 weeks at doses of 2.7-6.0g/day, which usually contained 50-100 mg ginsenosides/day [20,38].…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, ginseng's long‐lasting effects have been shown to be more beneficial in a disease state than a healthy state (Zhou et al, ). In vivo and in vitro studies report that ginseng might ameliorate inflammation in various inflammatory diseases including acute liver disease (Igami, Shimojo, Ito, Miyazaki, & Kashiwada, ), activated microglia in neurologic disorders (Rastogi, Santiago‐Moreno, & Doré, ), colitis (Lee, Hyam, Jang, Han, & Kim, ; Lee, Jeong, Eun, & Kim, ), pulmonary diseases (Shergis et al, ), cancer (Helms, ), and diabetes (Hong, Ji, & Kang, ). Ginseng also is beneficial for cardiovascular diseases mainly due to its cardioprotective and antihypertensive effects (Karmazyn, Moey, & Gan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Korean Red Ginseng (KRG) has been traditionally prescribed for various diseases, although the exact mechanisms by which KRG mitigates the severity of diseases remain unclear [2]. Recent advances in understanding the pharmacological components of KRG shed light on identifying a variety of bioactive ingredients, such as ginsenosides, polysaccharides, phytosterols, peptides, polyacetylenic alcohols, and fatty acids, that prevent and eradicate diabetes, tumors, ulcers, aging, and depression [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%